The reliability of television broadcasting statistics in soccer - Worsfold, P.; Macbeth, K. (International Journal of Performance Analysis in Sport, 2009)
The aim of this study was to determine if match statistics provided by television companies are a reliable measure of performance. Statistics for six performance indicators were collated from thirty teams over fifteen soccer matches presented by four independent broadcasting companies. Independent post-match analysis was also conducted analyzing the same six performance indicators used by the broadcasting companies. Mean percentage error was calculated for each pair (10 pairs) of observations for each of the six performance indicators. Mean percentage errors above 10% and up to 59.51% were identified between television company statistics and the independent post-match analysis within five out of the six performance indicators assessed. It is possible that different analysis techniques, analyst errors, unclear referee signals and differing operational definitions contributed to the unexpected statistical variations. The study highlights the need for universally accepted performance definitions within soccer. Due to the variability in statistics between companies and the post-match data analysis, viewers and researchers should view television company statistical data with caution and only use the data as a guide to individual, team and match performance and not as an exact measure.